Semiotics Analysis in Shopee 9.9 Super Shoping Day Advertisement Hearts2hearts Edition - Dispensasiani Telaumbanua; Mirnawati Tambunan; Keisha Amanda Zendrato; Nia Lestari; Sarah Ariella (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study analyzes the semiotic meanings in Shopee’s 9.9 Super Shopping Day advertisement featuring the rookie idol group Hearts2Hearts. Using Roland Barthes’s concept of denotation, connotation, and myth, supported by Charles Sanders Peirce’s triadic model of sign (icon, index, and symbol), this research examines how visual and auditory elements construct cultural and emotional meanings. The study employs a qualitative descriptive method by observing and categorizing signs from the advertisement video. The findings reveal that Shopee uses orange color dominance, cheerful jingles, and synchronized choreography to symbolize happiness, energy, and emotional connection. These elements collectively create a myth that associates shopping with joy and efficiency. The advertisement also demonstrates Shopee’s shift toward localized idol representation to strengthen authenticity and audience engagement. This study contributes to the understanding of how semiotic strategies shape consumer perception in Southeast Asian digital advertising and highlights the importance of emotional branding in modern marketing. The results also suggest that semiotic analysis can provide deeper insights into how advertisements influence social values and consumer identity in contemporary media.